Resource-Based Model Of Cross-Cultural Literacy Development Of Future Tourism And Sports Tourism Inspectors - Kononets, Nataliia; Zhamardiy, Valeriy; Shkola, Olena; Mokliak, Volodymyr; Moskalenko, Oleksandr; Mirna, Nataliіa (My University, 2022)
The aim of the study is to develop and comprehensively present the components of the resource-based model of cross-cultural literacy development of future inspectors for tourism and sports tourism, which consists of three interconnected blocks: methodological-target, content-procedural and diagnostic-resultive, and is based on the concept of Resource-based learning. A pedagogical experiment was organized to test the effectiveness of the model. The pedagogical experiment lasted during 2019-2021 (ascertaining – 2019-2020, formative – 2020-2021). Methods: theoretical, empirical; experimental; statistical. The analysis of the results of the pedagogical experiment of the effectiveness of the implementation of resource-oriented model and pedagogical conditions for the development of cross-cultural literacy of future inspectors of tourism and sports tourism shows, that the high level of cross-cultural literacy of students in the control group (CG) increased by only 2.6 %, while in the experimental group (EG) it increased by 12.94 %; the average level in CG increased by 1.04 %, and in EG – by 16.92 %; low level in CG decreased by 3.65 %, and in EG – by 29.85 %.
Resource-Based Model Of Cross-Cultural Literacy Development Of Future Tourism And Sports Tourism Inspectors / Nataliia Kononets, Valeriy Zhamardiy, Olena Shkola, Volodymyr Mokliak, Oleksandr Moskalenko, Nataliіa Mirna // Journal for Educators, Teachers and Trainers, 2022. – Vol. 13(2). – P. 252–259 .
Keywords: ресурсне навчання, кроскультурна грамотність, розвиток, туризм, спортивний туризм, педагогічні умови, модель; resource-based learning, cross-cultural literacy, development, tourism, sports tourism, pedagogical conditions, model